Pelatihan Konten Digital Media Sosial sebagai Sarana Dakwah Remaja Masjid Purnawira Desa Ledug, Kabupaten Banyumas - Tenia Wahyuningrum; Nicolaus Euclides Wahyu Nugroho; Silvia Van Marsally; Naurah Qatrunnada; Ade Fakthul Anam (Universitas Prof. Dr. Moestopo (Beragama), 2026)
This community service program aimed to strengthen the digital literacy and content production skills of youth and mosque administrators at Masjid Purnawira Ledug, Banyumas. The main problem faced by the partner was the limited use of social media as a medium for mosque information and digital da'wah, although participants already had access to smartphones and were familiar with digital platforms. The activity was implemented through a participatory action research approach consisting of coordination, training, guided practice, publication planning, and evaluation. Training materials covered digital da'wah ethics, basic smartphone photography and videography, and simple content production for social media. Evaluation was conducted through paired pretest and post-test scores for two topics: digital da'wah and photography-videography. The results showed positive changes in both topics. The average score for digital da'wah increased from 96.14 to 99.32, while the average score for photography-videography increased from 97.38 to 99.52. The participants were also actively involved in recording video practices around the mosque. The program indicates that mosque-based digital content training can support youth empowerment and improve the sustainability of mosque information management